Quantifiable impact of the Uruguay Round on pverty. - VAINIO, Matti (1996)
Summarises the most important effects of the Uruguay Round and analyses the effects of the Round on poverty. Concludes that while the implementation of the Uruguay Round agreements is projected to lead to an expansion of trade as well as to shifts in trade patterns, the quantifiable net effects on economic growth and poverty are likely to be small. Advises that developing countries should take advantage of the opportunities presented by the Uruguay Round to reduce poverty through trade, and to mitigate any negative effects on specific poverty groups.